Community Participation in Supervising State Finances in the Context of Realizing Good Governance - Rayhan, Ahmad; Muslih, Muhamad; kusumawardhani, adinda pramesty sulistya; Angel, Destyani (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
Public financial supervision carried out by the community is one form of good governance in Indonesia, the existence of public participation is one indicator of good governance. Public participation in a country, especially related to the supervision of state financial management, is urgent, this is because it is a form of check and recheck of the government in a democratic country. So researchers feel it is important to examine the role of public participation in the supervision of state financial management. The research method used is normative juridical. The results of this study are that the main responsibilities in public participation include: a) Participation in decision making b) Implementation Participation, c) Participation in utilization d) Participation in Evaluation. Public participation in the National PK Strategy consists of public participation in the formulation, implementation, monitoring, evaluation, and reporting of strategies. Participation in the implementation of national strategies can be achieved through various means, such as participation in forums, monitoring, evaluation, and creation of financial ownership databases. The community can contribute by ensuring sustainable political engagement, good governance, and simple procedures. This goal can be achieved faster if the community actively assumes responsibility in dealing with state institutions. The community has the highest sovereignty, so the quality of a government is also influenced by the community that elects state representatives. The community also plays a preventive role when proactive action is needed to instill the values of honesty and hatred of corruption through ethical messages and moral education as early as possible.